Comorbidity of ADHD and Major Depressive Disorder: Exploring Biological and Interpersonal Factors - Tu-Minh H Bui (Undergraduate Research Journal for the Human Sciences, 2025)
Abstract This literature review aims to synthesize and contextualize current research in ADHD and MDD across biological and interpersonal factors to assess how the two interplay. This is accomplished by assessing genetic disposition and neurobiological underpinnings alongside parent-child relationships and peer interactions to address interpersonal factors. The main queries used to search for peer-reviewed journal articles were “ADHD and depression” and “childhood ADHD and depression” across four databases: APA PsycARTICLES, PubPsych, PubMed, and MIT Cognet. Findings reveal that genetic factors contributing to hyperactivity and inattention also influence depressive traits. Neuroimaging studies revealed that individuals with ADHD and MDD comorbidity exhibit neurological structural and functional abnormalities. Environmentally, parents of children with ADHD are more likely to have children who develop MDD if they have poor mental health. Additionally, children with ADHD are more likely to be socially rejected by their peers, affecting their self-esteem and thus increasing the likelihood of developing MDD later in life. Understanding how these factors interplay is critical in accurately assessing the biological-environmental conditions of children with ADHD to determine their risk of developing MDD. As a result of these findings, clinicians should be vigilant in screening for depressive symptoms in individuals diagnosed with ADHD to facilitate early intervention, such as psychosocial training and social skills development, to reduce the likelihood of MDD later in life.
Keywords: ADHD; Major Depressive Disorder; Attention-Deficit/Hyperactivity Disorder; MDD; Comorbidity